The Impact of Environmental, Social, and Governance Disclosure on Financial Performance in Indonesian Mining Companies - Retnosari Retnosari; Erni Puji Astutik; Adella Vania Frimasika (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
ESG has become a strategic framework for sustainability, stakeholder engagement, and corporate value creation, while financial performance is commonly measured through profitability and market-based indicators. The purpose of this research is to examine how the disclosure of environmental, social, and governance information influences corporate financial outcomes in the mining sector. A quantitative approach was applied using multiple linear regression analysis on secondary data drawn from company reports. The results reveal that environmental disclosure has a significant positive effect on financial performance, as it enhances efficiency, reduces costs, and strengthens corporate reputation. In contrast, social and governance disclosures do not show a significant impact, indicating that their implementation remains largely formalistic and has not translated into measurable financial benefits. The findings highlight the importance of prioritizing environmental initiatives within ESG practices while suggesting the need for more substantive approaches to social and governance aspects. This study contributes to the literature by providing sector-specific insights and offering practical implications for companies seeking to align sustainability disclosure with financial value creation.